Pandemic Policing and Police Sexual Misconduct: Voices of Women Sexually Abused by COVID-19 Enforcement Officers - Aborisade, Richard A. (Women & criminal justice, 2024)
While global attention has been drawn to the reported spike in the rate of gender-based violence (GBV) occasioned by COVID-19 restrictions, there exists a clear gap in knowledge about incidences of GBV perpetrated by police officers in the course of enforcing COVID-19 laws. Drawing from the Nigerian experience, this qualitative study presents the accounts of 83 sexually victimized women. From the thematic analysis, their narratives of how COVID-19 lockdown facilitated their vulnerability to police sexual violence (PSV) were documented. Although the various forms of sexual violence experienced by the women during the lockdown are similar to pre-COVID PSV, in the current study, there appear to be more varieties of sexual violence, diverse tactics used by perpetrators, more factors determining vulnerability, and a greater opportunity structure for PSV. The findings highlight the need for revisiting existing models of PSV and reimagining governments’ policies in uncertain times to ensure public safety.